Reproductive toxicity potentials of methanolic extract of Portulaca oleracea in male rats: An experimental study - Izuchukwu Azuka Okafor; Uchenna Somtochukwu Nnamah; Selasie Ahiatrogah; Dorcas Serwaa; Jude Nnaka (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Purslane is an edible widely distributed shrub and one of the herbs used in decoctions for the treatment of different ailments including infertility. However, there is a shortage of evidence to validate its reproductive effects. Objective: To investigate the effect of methanolic extract of Portulaca oleracea (MEPO) on the reproductive system of male rats. Materials and Methods: Fifteen 10-wk old male Wistar rats with an average weight of 183 gr were randomly divided into three groups (n = 5/each). Group A (the control group) received distilled water only; group B received 400 mg/kg MEPO; and group C received 800 mg/kg MEPO for 14 days. The animals fasted overnight after the 14 th day of administration and euthanized by cervical dislocation. Blood samples, sperm, testes, and epididymis were collected for serum hormones, sperm, and histological analyses. Results: There was no significant change in the serum luteinizing hormone and testosterone levels across all groups when compared to the control. However, group C showed a significant increase (p = 0.020) in follicle-stimulating hormone levels when compared to the control. There was a significant reduction (p = 0.006) in the sperm count in group C when compared with the control group. There was also a significantly reduced (p = 0.003) sperm motility in MEPO-treated groups compared to the control. While the testis showed no abnormalities in its histoarchitecture across groups, the epididymis showed some blood congestion in MEPO-treated groups. Conclusion: Portulaca oleracea showed the ability to reduce sperm count and motility at higher doses.